GAMBARAN PENGETAHUAN GIZI DAN POLA MAKAN PASIEN RAWAT JALAN DIABETES MELLITUS TIPE-2 DI RUMAH SAKIT - Abdullah Tamrin; Sitti Sahariah Rowa; Chaerunnimah Chaerunnimah; M Irwansyah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: Knowledge of nutrition is the ability to understand the concepts and principles as well as information related to nutrition. Provincial health profile data south sulawesi in 2015, Diabetes Mellitus outpatients aged 40 years and above is 85%. Data on the record medic general hospital the area of a city makassar be seen that of diabetes mellitus in 2015 were 234 men and women 165.Objective: This research aims to describe the knowledge about nutrition and food consumption pattern among outpatients diabetes mellitus tipe-2 ( dm tipe-2 ) in a public hospital the area of a city Makassar.Method: Sampling done by purposive sampling criteria of Diabetes Mellitus patients visiting the hospital in June 2016 and suffered no complications.Result: The results of this study are patients with good nutritional knowledge are 48.6% and patients who have less nutritional knowledge are 51.4%. Patients who have food consumption pattern based on the frequency of good food is 42.9 % and 57.1% have less. Food consumption pattern based on the composition dishes of food in general is good which is 100%. Conclusion: Conclusions from this research is their knowledge about nutrition generally still less that is 51,4 % .Food consumption pattern based on the frequency of food is generally less that is 57.1 % , Food consumption pattern based on the composition dishes of food in general is good which is 100% and a %. Food consumption pattern based on a kind of food is generally good but lacking in fruits.Suggest: For side Hospital so that to schedule it illumination to patient Diabetes Mellitus about its important various of fruit to patient Diabetes Type Mellitus-2.Key Word : Nutrient Knowledge, eating Pattern, Patient Take care Way,Type DM-2